Lower and Upper Ordovician conodont biostratigraphy and revised lithostratigraphy in the fault and fold zones of the Boothia Uplift, south-western Boothia Peninsula, Nunavut - Zhang, Shunxin (Canadian Journal of Earth Sciences, 2023)
The strata exposed near Pasley Bay on south-western Boothia Peninsula were previously named the Franklin Strait Formation, spanning Lower Ordovician through early Silurian and dissected by two disconformities. The interpretation of the age and correlation were based on limited fossil evidence. New detailed field investigations and sampling at the Pasley Bay section resulted in a finding of over 1000 identifiable conodont specimens representing 37 species among 28 genera. Five Lower Ordovician and four Upper Ordovician North American standard conodont Zone-equivalent faunas are documented from the section, namely: Lower Ordovician Cordylodus angulatus, Rossodus manitouensis, Acodus deltatus/ Oneotodus costatus, Oepikodus communis, Reutterodus andinus, and Upper Ordovician Belodina confluens, Oulodus velicuspis, Oulodus robustus, and Amorphognathus ordovicicus Zone-equivalent faunas. These faunas enable a new understanding of the age and stratigraphic position of the Franklin Strait Formation: (1) it is now correlated to the Turner Cliffs (upper part of lower member and upper member), Ship Point, Thumb Mountain, Irene Bay, and Allen Bay (lower member) formations straddling Lower to upper Upper Ordovician with the Middle and lower Upper Ordovician missing; (2) it biostratigraphically overlaps with the simultaneously named Netsilik Formation for the strata containing the Cordylodus angulatus, Rossodus manitouensis, Acodus deltatus/Oneotodus costatus, and lower Oepikodus communis Zone-equivalent faunas, and lithostratigraphically for the upper part of lower member and upper member of the Turner Cliffs Formation and lower Ship Point Formation. This study also provides stratigraphic support for the tectonic model that advocates the Boothia Uplift to be a deep-seated, east-dipping thrust block. Additionally, the conodont Colour Alteration Index is used to estimate the increased heat effects close to the fault zones in the environs of the Boothia Uplift.